Synthesis, Chiral Resolution, and Absolute Configuration of C2‐Symmetric, Chiral 9, 9′‐Spirobifluorenes. Issue 29 (29th August 2014) - Stobe, Caroline; Seto, Ryota; Schneider, Andreas; Lützen, Arne
Abstract: Racemic 2, 2′‐, 2, 2′, 7, 7′‐, and 2, 2′, 3, 3′‐substituted 9, 9′‐spirobifluorenes were synthesised and successfully resolved by HPLC on a Chiralpak IA stationary phase on both analytical and semipreparative scales. Their absolute configurations were determined by comparison of their specific optical rotations with literature data or by comparison of retention times with independently prepared enantiopure material. These compounds are versatile C 2 ‐symmetric building blocks for the formation of more sophisticated cleft‐like, chiral molecular architectures. Abstract : Dissymmetric difunctionalised 9, 9′‐spirobifluorene derivatives were prepared and resolved by HPLC on a chiral stationary phase on a semipreparative scale. The absolute configurations of the resolved enantiomers were assigned by comparison of specific optical rotations with literature data or retention times of independently prepared enantiomerically pure material.